Application of a risk management tool focused on helping to small and medium enterprises implementing the best practices in software development projects (2018)
Today, SMEs (small and medium enterprises) face difficulties implementing best practices contained in standards and models internationally accepted such as CMMI, ISO, PMBOK, because they lack of economic resources, human resources, skills, tools and techniques focused on the implementation of best practices, in addition, to apply the best practices provided by these models and standards, the SMEs require to adapt them according to their size and type of business. This research work aims to present the results of a case study of the application of the tool that performs basic risk management in in 2 companies. The results show that both of them perceived the use of the tool as useful to implement software engineering best practices in an easy way. © Springer International Publishing AG, part of Springer Nature 2018.